Editors' Note: Cognitive Outcome 1 Year After Mild Traumatic Brain Injury: Results From the TRACK-TBI Study. (25th October 2022) - Ganesh, Aravind; Galetta, Steven
Abstract : Dr. Schneider et al. examined cognitive outcomes 1 year after mild traumatic brain injury (mTBI) in 665 participants compared with 156 healthy controls in a prospective cohort study, Transforming Research and Clinical Knowledge in TBI. They found that poor 1-year cognitive outcome was common, affecting 13.5% of patients with mTBI vs 4.5% of controls, highlighting the need for better understanding of mechanisms underlying poor cognitive outcomes in this population to improve their recovery. In response, Dr. Tsao wonders whether outcomes would have been different if including only patients with a Glasgow Coma Scale (GCS) score of 15 (as opposed to the more inclusive GCS 13–15 definition used in the study) or if examining a population not seeking immediate treatment (unlike those presenting to an emergency department in this study). He also notes that the proportion of healthy controls with poor cognitive outcome during the study was higher than expected, given the average age of 37 years, and wonders whether the multiple patients who showed a borderline decline in the cohort are at a higher risk of future cognitive impairment or dementia. Responding to these comments, the authors agree that a stricter definition of mTBI may be considered by other researchers and clarify that their definition of poor cognitive outcome included both norm-based cognitive impairment and clinically meaningful decline, with less than 2% of controls meeting criteria for the latter—potentially a higher-risk group—whereas the remaining controls with apparent poor outcome may reflect expected noise and the limits of test-retest reliability. This exchange underscores our evolving understanding of the burden of cognitive decline in patients with mTBI.